Draft of the Constitution of the National Organization for the Professional Advancement of Black Chemists and Chemical Engineers - National Organization for Black Chemists and Chemical Engineers (1975)
Preliminary constitution of the National Organization for the Professional Advancement of Black Chemists and Chemical Engineers (NOBCChE) with handwritten notes by an unknown author.
Keywords: National Organization for Black Chemists and Chemical Engineers; Constitutions; African American chemists; Chemists; Chemical engineers; African American engineers